Control strategies for automatic gantry crane system - Jalani, Jamaludin (2005)
Gantry crane is a machine that moves payload from one point to another point. Nowadays, most of gantry cranes use open loop system to control position while antiswing control is operated manually by skillful operators. The open loop system is sensitive to the parameter variations and disturbances while operator's skills are restricted by fatigue problem and will affect the performance of the gantry crane. In order to overcome the problems, feedback control is adopted in this study. Firstly, classical PID and PD were introduced as position and anti-swing control respectively. The experimental result showed that the PID and PD controllers were successfully controlled both position and swing of the gantry crane especially for small load displacement. However, the positioning performance was degraded due to the saturation of the actuator. In addition, the PID controller design is a time consuming process, since model and parameters of the gantry crane are needed. Secondly, nonmodel based of fuzzy logic controllers are implemented in the gantry crane system for position and anti-swing control. The experimental result showed that fuzzy logic controllers had resulted on good performances for anti-swing controller. However, the results for position control were inconsistent for small desired position. The tuning process may improve the control performance but it may affect other desired positions. Finally, non-model based of NCTF controller, was proposed for position control of the gantry crane system while the anti-swing control by using fuzzy logic controller remained the same since it gave good performance. The experimental result showed that the NCTF controller produced best results for position control of the gantry crane system compared to other controllers.